2020
DOI: 10.3390/foods9050654
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Attitude to Consumption of Rabbit Meat in Eight Countries Depending on the Production Method and Its Purchase Form

Abstract: The study’s aim was to investigate the consumers’ attitude to their preference of rabbit meat in eight countries depending on the production method and its purchase form. In Spain and China almost all factors got low scores. High scores (above 4 out of 5) for origin were found in Italy, France, Poland, Hungary and Brazil. The importance of feeding was highlighted in Italy, Poland, Hungary and Mexico. High values were received for housing conditions in Italy, Poland, Hungary and Mexico. The level of processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 32 publications
1
34
0
3
Order By: Relevance
“…These results confirm those of previous studies in other geographical contexts, which show that there is a relationship between rabbit meat consumption and age, gender and occupational status (McLean-Meyinsse, 2000;Beal et al, 2004;González-Redondo, 2010). In contrast to our findings, in a recent study on consumers' attitude to rabbit meat consumption in eight countries, Szendrő et al (2020) found a statistically significant coefficient between consumption frequency, age and gender…”
Section: Consumption Frequency According To Sociogeographic Variablessupporting
confidence: 91%
See 2 more Smart Citations
“…These results confirm those of previous studies in other geographical contexts, which show that there is a relationship between rabbit meat consumption and age, gender and occupational status (McLean-Meyinsse, 2000;Beal et al, 2004;González-Redondo, 2010). In contrast to our findings, in a recent study on consumers' attitude to rabbit meat consumption in eight countries, Szendrő et al (2020) found a statistically significant coefficient between consumption frequency, age and gender…”
Section: Consumption Frequency According To Sociogeographic Variablessupporting
confidence: 91%
“…Differences were considered statistically significant at a level of P<0.05. Examples of this methodology can be found in (Beal et al, 2004;Mailu et al, 2017;Islam et al, 2018;Montero Vicente et al, 2018;Szendrő et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (83%) of production is in Spain (48.5 million rabbits slaughtered), followed by France (29 million rabbits slaughtered) and Italy (24.5 million rabbits slaughtered). Rabbit meat represents a traditional dietary practice in the Mediterranean area and a new source of consumption in China and Mexico [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has a long tradition of rabbit meat production and consumption in France, Italy and Spain, and according to the database of FAOSTAT [27] the world per capita rabbit meat consumption in 0.242 kg, while it is very high in many European countries, expecially 4.39 kg per capita in Italy. It presents the stable growth of rabbit meat consumption state from 2000 to 2013 in many European countries [28]. rabbit meat offers excellent nutritive and dietetic properties [29] and contais high-quality protein, low fat, low cholesterol, which is ideal meat of the obese and cardiovascular patients.…”
Section: Introductionmentioning
confidence: 99%